The Impact of Using Artificial Intelligence In The Process of Preparing Financial Statements - Dwi Siyamsih; Eko Cahyo Mayndarto (Pt. Anagata Sembagi Education, 2025)
This study explores the impact of Artificial Intelligence (AI) on the preparation of financial statements and its influence on the quality of financial reporting. The research applies a quantitative descriptive-explanatory method, using a purposive sampling technique involving 60 accounting and finance professionals from organizations that implement AI-based systems in their reporting processes. Data were collected through structured questionnaires and analyzed using multiple linear regression to examine the relationship between AI usage and the quality of financial statements, measured through indicators such as reliability, relevance, and comparability. The findings show that AI has a positive and statistically significant effect on financial reporting quality. This indicates that greater integration of AI tools in accounting processes can enhance the accuracy, consistency, and decision-usefulness of financial information. The results not only confirm the practical benefits of AI in streamlining financial tasks but also contribute to the theoretical understanding of how digital technologies are reshaping the foundations of accounting practices. By positioning AI as a transformative force in the evolution of financial reporting theory, this study provides a basis for future research to explore the broader implications of AI adoption, particularly in areas such as audit automation, ethical standards, and the development of digital accounting frameworks.